Preservation and Significance of Extracellular DNA in Ferruginous Sediments from Lake Towuti, Indonesia - Vuillemin, Aurèle; Horn, Fabian; Alawi, Mashal; Henny, Cynthia; Wagner, Dirk; Crowe, Sean A.; Kallmeyer, Jens (Frontiers in Microbiology, 2017)
Extracellular DNA is ubiquitous in soil and sediment and constitutes a dominant fraction of environmental DNA in aquatic systems. In theory, extracellular DNA is composed of genomic elements persisting at different degrees of preservation produced by processes occurring on land, in the water column and sediment. Extracellular DNA can be taken up as a nutrient source, excreted or degraded by microorganisms, or adsorbed onto mineral matrices, thus potentially preserving information from past environments. To test whether extracellular DNA records lacustrine conditions, we sequentially extracted extracellular and intracellular DNA from anoxic sediments of ferruginous Lake Towuti, Indonesia. We applied 16S rRNA gene Illumina sequencing on both fractions to discriminate exogenous from endogenous sources of extracellular DNA in the sediment. Environmental sequences exclusively found as extracellular DNA in the sediment originated from multiple sources. For instance, Actinobacteria, Verrucomicrobia, and Acidobacteria derived from soils in the catchment. Limited primary productivity in the water column resulted in few sequences of Cyanobacteria in the oxic photic zone, whereas stratification of the water body mainly led to secondary production by aerobic and anaerobic heterotrophs. Chloroflexi and Planctomycetes, the main degraders of sinking organic matter and planktonic sequences at the water-sediment interface, were preferentially preserved during the initial phase of burial. To trace endogenous sources of extracellular DNA, we used relative abundances of taxa in the intracellular DNA to define which microbial populations grow, decline or persist at low density with sediment depth. Cell lysis became an important additional source of extracellular DNA, gradually covering previous genetic assemblages as other microbial genera became more abundant with depth. The use of extracellular DNA as nutrient by active microorganisms led to selective removal of sequences with lowest GC contents. We conclude that extracellular DNA preserved in shallow lacustrine sediments reflects the initial environmental context, but is gradually modified and thereby shifts from its stratigraphic context. Discrimination of exogenous and endogenous sources of extracellular DNA allows simultaneously addressing in-lake and post-depositional processes. In deeper sediments, the accumulation of resting stages and sequences from cell lysis would require stringent extraction and specific primers if ancient DNA is targeted.